Machine learning exploratório em atletas masculinos de alto nível de jiu-jitsu sugere a revisão da categoria absoluto a partir da força de preensão manual - Verli, Márcio Vinícius de Abreu (2024)
Jiu-jitsu, also known as the "gentle art", is recognized as the first fighting style that does not use weapons, created essentially for self-defense, using levers, throws, twists and immobilizations as combat tools. Over time, and in search of a way to make the sport fairer, rules were created to divide categories. Among these rules are the specifications of the fights, using age, gender, weight and rank (belts) as a way to separate the categories. During the fight, jiu-jitsu athletes face each other in constant physical contact with their opponent, always seeking a position of superiority, making them maintain successive gripping movements, thus demonstrating the importance of promoting strength during the practice of this sport. Therefore, in addition to the technical and tactical aspects, handgrip strength is a differential for good performance, since the need to control and sustain the “grip” during the fight, performing positions to control space and move the opponent are essential, with many authors considering it as a determining factor during the fight, also defining it as a parameter of utmost importance to differentiate the performance and performance of competitors. Specific literature already points out that, with the specific characteristics of each fighting category, evaluations are necessary that separate each athlete into their category, treating each category differently, especially considering that there is a category (absolute) where all athletes compete without separation by weight, which may result in a significant difference in the evaluation standards between each athlete. Therefore, the objective of the present study was to evaluate whether the current separation of fighting weight categories is ideal, taking into account handgrip strength. This is a cross-sectional, descriptive and observational study, with adult athletes competing in jiu-jitsu. The participants were 206 adult jiu-jitsu athletes. The procedures evaluated were height, body mass and handgrip strength. The results suggest that, taking into account handgrip strength, athletes in the absolute category should be separated into 4 subcategories. The present study suggests a review of the weight and age categories in jiu-jitsu competitions for the “absolute” category, favoring competitions with more homogeneous categories and with greater competitiveness and broad competition without discrepancies in the strength of their practitioners. Therefore, we suggest the creation of four subcategories, as shown by the data from the present study.